2012
DOI: 10.1021/ac301829t
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Kinetic Capillary Electrophoresis for Studies of Protein–Small Molecule Interactions

Abstract: Kinetic capillary electrophoresis (KCE) is a toolset of homogeneous affinity methods for studying kinetics of noncovalent binding. Sensitive KCE measurements are typically done with fluorescence detection and require a fluorescent label on a smaller-sized binding partner. KCE with fluorescence detection is difficult to use for study of protein-small molecule interactions since labeling small molecules is cumbersome and can affect binding. A combination of KCE with mass-spectrometry (KCE-MS) has been recently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Advantageously,A CTIS can be combined with any detection method which 1) can be coupled with acapillary,2)uniformly integrates the signal through the capillary cross-section, 3) has sufficiently high signal readout speed, and 4) has ac oncentration limit of quantitation below the K d values of the studied complexes.Acombination of ACTIS with MS appears to be the most suitable one for protein-small molecule complexes as it allows label-free detection of small molecules.However, because of matrix effects on ionization, [26] ACTIS-MS requires reasonably pure protein solutions.W hile TIS is not sensitive to buffer composition, MS is.T herefore,v olatile buffers are preferable over nonvolatile buffers for ACTIS-MS.I th as been previously shown that volatile buffers are suitable for studies of biomolecular interactions provided that they can support required pH and ionic strength. [27] If TIS is conducted in an onvolatile buffer, the sample should be diluted at the capillary exit with as heath liquid suitable for both dissociation of the protein-ligand complex and efficient ionization of the ligand. In general, we foresee that most of the future technical development of ACTIS will deal with its coupling to different detection systems and satisfying the four above-listed ACTIS requirements for detection systems.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Advantageously,A CTIS can be combined with any detection method which 1) can be coupled with acapillary,2)uniformly integrates the signal through the capillary cross-section, 3) has sufficiently high signal readout speed, and 4) has ac oncentration limit of quantitation below the K d values of the studied complexes.Acombination of ACTIS with MS appears to be the most suitable one for protein-small molecule complexes as it allows label-free detection of small molecules.However, because of matrix effects on ionization, [26] ACTIS-MS requires reasonably pure protein solutions.W hile TIS is not sensitive to buffer composition, MS is.T herefore,v olatile buffers are preferable over nonvolatile buffers for ACTIS-MS.I th as been previously shown that volatile buffers are suitable for studies of biomolecular interactions provided that they can support required pH and ionic strength. [27] If TIS is conducted in an onvolatile buffer, the sample should be diluted at the capillary exit with as heath liquid suitable for both dissociation of the protein-ligand complex and efficient ionization of the ligand. In general, we foresee that most of the future technical development of ACTIS will deal with its coupling to different detection systems and satisfying the four above-listed ACTIS requirements for detection systems.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Three volatile BGEs (ammonium acetate, ammonium bicarbonate, ammonium formate) were tested for the protein-ligand pair and compared to a physiological Tris-acetate BGE. Equilibrium-dissociation constants were obtained, and thus the possibility of coupling a volatile KCE method with MS detection was proved [78].…”
Section: Laser-induced Fluorescencementioning
confidence: 99%
“…Therefore, volatile buffers are preferable over nonvolatile buffers for ACTIS‐MS. It has been previously shown that volatile buffers are suitable for studies of biomolecular interactions provided that they can support required pH and ionic strength . If TIS is conducted in a nonvolatile buffer, the sample should be diluted at the capillary exit with a sheath liquid suitable for both dissociation of the protein–ligand complex and efficient ionization of the ligand.…”
Section: Figurementioning
confidence: 99%